Public Trust in the Effectiveness of the Covid-19 Vaccine in Liliba Village, Oebobo District, Kupang City - Aty, Yoany M. V. B.; Selasa, Pius; Molina, Marselina Bende; Mochsen, Rohana; Pupuh, Nantiya; Cholsakhon, Panyada (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
The Covid-19 pandemic has continued to develop in Indonesia since the beginning of 2020. The incidence and death rates continue to increase from day to day. Various efforts were made to stop the spread of the deadly Covid-19. One way to prevent and suppress the spread of infection with the virus is to vaccinate. The role of the vaccine is to provide immunity. Many people in the city of Kupang do not believe in the effectiveness of the Covid-19 vaccine, so they do not want to be vaccinated. The objective of this study is to describe the level of public confidence in the effectiveness of the Covid-19 vaccine in Liliba Village, Oebobo District, Kupang City. The research method is quantitative with a descriptive study research design. The population is people who live in the Liliba sub-district, Oebobo district, Kupang City. The sample was 106 people who were taken using the Cluster Simple Random Sampling technique. The results showed that the level of public confidence in the susceptibility of the Covid-19 vaccine was (89.6%), the seriousness of the vaccine's effectiveness (90.6%), the benefits of the vaccine (54.7%), and the perceived barriers (88.7%). This study revealed that the level of public confidence in the effectiveness of the Covid-19 vaccine in Liliba Village, Oebobo District, Kupang City is high.